Chemoport Insertion as Minimal Chemotherapy Access Complications and Forms of Patient Safety Implementation Goal - Istri Anom, T; ., Rusdi; Chalik Sjaff, A; Wibowo, A (KnE Life Sciences, 2018)
Chemotherapy access measures in cancer patients can be done through 2 (two) ways, using abocath as peripheral intravenous access and insertion of chemoport under the skin. For patients undergoing chemotherapy with long treatment durations, it is necessary to use chemoports to prevent patients from some peripheral intravenous side effects, one of them being extravasation. This surgery is performed in the operating room and is based on the patient’s safety standards. In 2016, while performing digestive surgeries chemoport insertion was done in 18 patients with a diagnosis of colorectal cancer. Most of the patients were elderly (66.7%) and only 3 (three) patients had complications of catheter blockage and infection in the chemoport insertion area. This suggestion was caused by the reduction in the elasticity of blood vessels in elderly people. So, it is advisable to do chemoport insertion. If complications occur, the blockage can be prevented by flushing. Meanwhile, if there is an infection complication, it is advised to immediately release the chemoport and give antibiotic when necessary. The day before the surgery, the surgeon must verify the patient’s condition, marking the operating area as well as carrying out the time out procedure before the chemoport insertion operation begins. Chemoport insertion is an action that can be done to facilitate chemotherapy access especially for patients undergoing chemotherapy in long periods, and it has minimal complications. Keywords: chemoport, chemotherapy, patient safety